2019
DOI: 10.1186/s12915-019-0633-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sea star larval regeneration reveals conserved processes of whole-body regeneration across the metazoa

Abstract: Background Metazoan lineages exhibit a wide range of regenerative capabilities that vary among developmental stage and tissue type. The most robust regenerative abilities are apparent in the phyla Cnidaria, Platyhelminthes, and Echinodermata, whose members are capable of whole-body regeneration (WBR). This phenomenon has been well characterized in planarian and hydra models, but the molecular mechanisms of WBR are less established within echinoderms, or any other deuterostome system. Thus, it is n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 88 publications
2
75
2
Order By: Relevance
“…The first of these points is consistent with the evidence on the molecular invariance of morphogenetic processes (i.e., various types of morphogenesis involve similar regulatory cascades) (Cary et al, 2019;Mehta and Singh, 2019). The second point (existence of "principal regulator" genes) is less evident; notable examples include fgf20 proposed as a primary regulator of fin regeneration in Danio rerio (Whitehead et al, 2005;Poss, 2010).…”
Section: The Origins Of Regenerationsupporting
confidence: 72%
“…The first of these points is consistent with the evidence on the molecular invariance of morphogenetic processes (i.e., various types of morphogenesis involve similar regulatory cascades) (Cary et al, 2019;Mehta and Singh, 2019). The second point (existence of "principal regulator" genes) is less evident; notable examples include fgf20 proposed as a primary regulator of fin regeneration in Danio rerio (Whitehead et al, 2005;Poss, 2010).…”
Section: The Origins Of Regenerationsupporting
confidence: 72%
“… Li et al (2015) showed that an amhy knockout resulted in male to female sex reversal in XY tilapia, while its over-expression resulted in female to male sex reversal; thus, validating amhy as the sex-determining gene in tilapia. We suggest that in a similar manner, the fshr candidate gene for SD should be further explored by functional validation using advanced methods, such as CRISPR/Cas9, TALEN, or antisense RNA ( Ventura and Sagi 2012 ; Li et al 2015 ; Bao et al 2019 ; Pan et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The few data available on "stemness" markers are not related to adult regeneration but to that of the bipinnaria larvae of Patiria miniata, where a vasa gene has been identified (Oulhen et al, 2016). Recent work has also shown that genes involved in a diverse array of pathways are expressed during anterior and/or posterior larval regeneration at different stages (Cary et al, 2019), suggesting that molecular signaling commonalities might exist between sea star larval regeneration and whole body regeneration of other metazoans.…”
Section: Asteroideamentioning
confidence: 99%
“…BrdU and EdU pulse/chase labeling of proliferating cells also give insight into not only division dynamics but also lineage and cell fate, particularly if fine control in labeling only a few cells is exercised. Comprehensive experiments are still lacking in many regenerating animals (but see Mashanov et al, 2013;Jeffery, 2015b;Cary et al, 2019), and are somewhat limited in scope, but do offer the advantage of not requiring extensive resources, and labeling is not affected by the changes in transcriptional or epigenetic state that occur during reprograming. Stable transgenic animals, or genetic labeling with inducible systems, permit by far the best control and resolution, and will be required to truly show changes in differentiation state and potency.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%